Implementasi Metode Pembelajaran Survey, Question, Read, Recite, Review Belajar IPA Materi Pokok Klasifikasi Materi dan Perubahannya di Kelas VII-4 SMP Negeri 1 Pujut - Mustikawati Mustikawati (Universitas Pendidikan Mandalika, 2020)
The purpose of this study is to improve student learning outcomes by implementing Survey, Question, Read, Recite, Review (SQ3R) learning methods in an effort to improve science learning outcomes on the subject matter of material classification and changes in grades VII-4 of SMP Negeri 1 Pujut. The research method uses classroom action research methods which consist of 2 action cycles. Each cycle consists of four stages including planning, implementation, observing the results of actions, and reflection. The number of students 31 students consisted of 17 male students and 14 female students. Based on the results of this study it can be concluded that there is a significant increase in student learning outcomes. This increase can be seen from the classical completeness obtained in the first cycle that is equal to 67.74% and the second cycle increased to 90.32% with an increase of 22.58%. This increase can also be seen from the observations of the activities of the first cycle teacher of 13 with a good category at an increase to 17 with a very good category in the second cycle. Whereas student activity in cycle I was 50 with active categories, increasing to 67 with very active categories in cycle II.